Nairability: a simple guide to money - Egbuna, Ngozi (Ngozi Egbuna, 2021)
Nairability follows this genre of literature with a straightforward and easy to read guide which provides teaching tools and engaging illustrations to capture the attention of its young readers. The book also goes further to provide development charts for parents to aid discussions with their children depending on the child's stage of development
Includes bibliographical references
osc 30/11/22
Loans
Keywords: Finance - personal; Nigeria